Technical-Economic Analysis of Photovoltaik Reverse Osmosis Planning for Fulfillment of Fresh Water System on Ro-Pax Ship - Jadmiko, Edi; Musriyadi, Tony Bambang; Amiadji; Ahmad, Dian Nafi’ (International Journal of Marine Engineering Innovation and Research, 2025)
The need for fresh water in the world of industry is increasing with the rapid development of the global industry. The shipping industry is having a significant impact as part of a global industry concerning the sector of freshwater demand on ships. Freshwater supplies on ro-pax vessels are very important because they are the source of crew and passenger life when ships sail. Fulfillment of freshwater needs on a ro-pax vessel is made in a conventional system by filling clean water into a freshwater tank from the port. In this final project will be analyzed technical and economical on designing fresh water system using reverse osmosis system with solar panel as power supply and compare it with conventional system on ship KM. SABUK NUSANTARA 56. This Final Project includes installation design, size of fresh water tank, amount of cargo, investment cost and operational cost. The conclusion obtained in this final project is a reverse osmosis (RO) system with solar panels as a very efficient power supply when applied to ro-pax ships such as ships KM SABUK NUSANTARA 56 because with this system the ship is able to produce their own fresh water, the size of the freshwater tank is smaller, for new shiploads can be increased. For the percentage of total cost of fresh water needs is dearer about 52 percent compared to conventional system and payload value increased 29.2 percent compared to conventional system.